Efficacy and effectiveness of COVID-19 vaccines: Progress and prospect - Yifan Li; Jiahai Lu (​​​One Health Bulletin, 2021)
To prevent and control COVID-19, COVID-19 vaccines are being developed, tested, and approved at an unprecedented rate. As of September 24, 2021, 22 types of COVID-19 vaccines have been approved for conditional marketing or emergency use by at least one country worldwide. Vaccine efficacy/effectiveness is a crucial concern for vaccination. This article provides an overview of efficacy of phase III clinical trials, vaccination, effectiveness of real-world studies as well as challenges of COVID-19 vaccine.